Budidaya Ayam-Ikan Terintegrasi Dalam Pembangunan Ekonomi Masyarakat Desa Nyogan Kecamatan Mestong - Muhammad Afdal; Hutwan Syarifuddin; Mairizal Mairizal (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2019)
Abstract The aim of the service activity was to develop the economy of Nyoga Community through the cultivation of integrated fish broiler.Due to the successfulness of the previous service program in year 2017 concerning the cultivation of Tilafia and catfish with farmer group (Kelompok Usaha Bersama (KUBE)) Mina Jaya dan Harapan Makmur in Nyogan village, the next program was to tried to apply the cultivation program of integrated fish and broiler by participation method from all of members of KUBE. Like previous program, the method was to involve all the group member of KUBE. Group member prepared the chicken pen above the fish pond and service team from University of Jambi granted the breed of fish and chicken. The result showed the good achievement with the increase of community interest of the KUBE to self-financingly build more unit of box fish nets Keyword : Nyogan, catfish, tilafia, integrated system, broiler